Risk factors for maternal colonization with group B beta-hemolytic streptococci - Terry, Richard R; Kelly, Francis W; Gauzer, Cheryl; Jeitler, Melissa (Journal of Osteopathic Medicine (Online), 1999)
Colonization with group B beta-hemolytic streptococci (GBS) at any time during pregnancy is an important risk factor for neonatal sepsis. To determine which groups of pregnant women are at high risk for GBS, a retrospective chart review was conducted on 608 pregnant women who had recorded data on prenatal charts and were seen between October 1995 and December 1997 at a family practice-run prenatal clinic. A total of 543 subjects were studied after exclusion of women who had no results of GBS colonization recorded. Demographically, the study population comprised 91.1% white non-Hispanic, 4.8% African-American, 1.5%Asian, and 2.6% white Hispanic women; 28.9% were primiparas, 38.9% unmarried; 60.0% low income; 31.1 % smokers, 7.7% with a history of drug or alcohol use; 8.4% with a history of sexually transmitted disease; and 27.2% with fewer than 11 prenatal visits. The mean age was 26.4 years (range, 14 to 42 years). Seventy-six (14.0%) of the study subjects were colonized with GBS. White non-Hispanic women had a GBS colonization prevalence of 13.6%; for all others, prevalence was 18.7%. No statistically significant differences were found in regard to age, weight, number of prenatal visits, income level, marital status, history of drug use, or parity. The GBS colonization rate for smokers was 33.1 % versus 16.4% for nonsmokers (P=.012). Maternal colonization of GBS was not found to be associated with any of the risk factors studied, other than smoking. This study identified smoking as a possible risk factor for GBS infection. Routine screening for GBS infection during pregnancy may be beneficial because no strong risk factors for colonization exist.